17.2k views
1 vote
-1 5/12 - 7/12 what is the answer

User Vctlzac
by
5.8k points

1 Answer

0 votes

To solve the exercise, we can first convert the first addend to an improper fraction:


1(5)/(12)=(1\cdot12+5)/(12)=(12+5)/(12)=(17)/(12)

Now we have a sum of homogeneous fractions. Homogeneous fractions are those that have the same denominator. To add these fractions, the numerators are added, and the denominator is left the same. So, we have:


\begin{gathered} -1(5)/(12)-(7)/(12)=-(17)/(12)-(7)/(12) \\ -1(5)/(12)-(7)/(12)=(-17-7)/(12) \\ -1(5)/(12)-(7)/(12)=(-24)/(12) \\ \boldsymbol{-1(5)/(12)-(7)/(12)=-2} \end{gathered}

Therefore, the result of the given operation is -2.

User Ivan Smetanin
by
6.1k points